Analyse et exploitation de la variabilité gestuelle dans la prévention des TMS - Marion Brunet; Jacques Riff (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article presents a study of the gestic variability of workers on an assembly line. It is part of an MSD prevention process and its aim is the collective and individual construction of health.The paper begins with a theory emphasizing the situated nature of movements, which are described in detail and studied from the standpoint of their determinants, sensations and operational logic. The methods combine participant observation and interview data as well as observations at the workstations and about videos. Different types of variability were identified (how to control one’s work, use tools, coordinate the movement of one’s arms). The analyses were used in MSD prevention by mainly promoting the operators’ attention and deliberation about their movements. Reflection on the concept of gestic variability and its formalization is proposed. Finally, we consider the conditions necessary for systematizing the analyses as well as means for evaluating the effects of this type of study.